SISTEM INFORMASI PELAYANAN PENGADILAN MILITER I-03 PADANG BERBASIS WEBSITE - Fandri Ernisa Putra Ernis; JUSMITA WERIZA (JENTIK, 2025)
The service system at the I-03 Padang Military Court in submitting services is using the SAIYO application (Online Service Information Administration System). The SAIYO application is an online service that utilizes the business whatsapp application or whatsapp group to apply for services at the Miluter Court I-03 Padang. The process of submitting the SAIYO application service is carried out in stages and the creation of the SAIYO application service report is made conventionally. Therefore, a Website-Based Service Information System was designed with the System Development Life Cicle (SDLC) system design method using the waterfal method, namely needs analysis, design, implementation, testing, maintenance, and tools for designing the Unified Modelling Langguage (UML) system which requires a Use Case Diagram, Activity Diagram, Class Diagram, Sequence Diagram. The methods in this study are observation, interviews and literature studies. The result of this research is that the Website-Based Service Information System is expected to help in the process of submitting services and making service reports accurately and accurately.